ANALYSIS OF ONLINE PROSTITUTION CRIMINAL ACTIONS REVIEWED FROM CRIME PREVENTION THEORY - Purborini, Vivi Sylvia; Rumadi, Rumadi (Gapenas Publisher, 2024)
Indonesia is one of the countries whose technology and information development is growing rapidly. The problem of prostitution is a complex problem, therefore this problem really needs special attention from the community. Prostitution, a business that is identical to the black world, is one of the businesses that generates money quickly. Online prostitution cases in Indonesia require a mitigation effort in overcoming online prostitution cases that occur. The meaning of the word mitigation itself is a process or method carried out to prevent, face or overcome a situation while trying to improve the behavior of someone who has committed a behavior that is declared guilty. This research is a normative legal research that is descriptive analytical in nature. This research approach uses a statutory approach. The data sources used in this study were taken from secondary data including primary legal materials, secondary legal materials, and tertiary legal materials. The secondary data collection technique used is a literature study. The data obtained is then analyzed qualitatively. The theory for overcoming crime has two ways, namely by means of preventive action (the occurrence of a crime) and repressive action (efforts after the occurrence of a crime). Preventive action is an action taken to prevent or guard against the possibility of a crime occurring